Deteksi Gen HptII dan Keragaan Agronomis pada Populasi BC1F1 Tanaman Padi Transgenik - Budi Santosa; Kurniawan R. Trijatmiko; Tri J. Santoso (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2013)
Rice varieties tolerant to drought stress are needed tostabilize rice production under drought stress condition. Wedeveloped transgenic rice cv. Nipponbare carrying hptIIgene that might also contain OsDREB1A gene. OsDREB1Agene responsible to drought tolerance trait need to betransferred into cultivated rice in order to obtain new localrice variety tolerant to drought stress. The aims of thisresearch were to detect the presence of hptII gene in the F1and BC1F1 transgenic rice and to observe the agronomicperformace of those populations and their plant physiology.F1 population was developed by crossing transgenicNipponbare, as donor parent, with Batutegi, Code, Ciherang,and Konawe genotypes, as recipient parents. BC1F1population was developed by backcrossing F1 transgenicline with recipient parents, respectively. The presence ofhptII gene was analyzed by PCR using a pair of primers forhptII. The observation of agronomic performance wascarried out in the green house, meanwhile the observationof stomata was done using microscope. The result of PCRanalysis showed that BC1F1 Batutegi trans, BC1F1 Code trans,BC1F1 Konawe trans1, BC1F1 Konawe trans3, dan BC1F1Konawe trans4 were detected carrying the hptII gene.Agronomic data showed that BC1F1 transgenic rice linesyielded panicles, filled grains, and total grains higher thanthose of recipent parents. Comparing to the recipientparents, BC1F1 Konawe trans1 and BC1F1 Konawe trans3 hadless stomata on the lower side of the leaf, but had morestomata on the upper side of the leaf.